Polymorphisms of two loci at the oxytocin receptor gene in populations of Africa, Asia and South Europe. Issue 1 (December 2016) - Butovskaya, Polina; Lazebny, Oleg; Sukhodolskaya, Evgeniya; Vasiliev, Vasily; Dronova, Daria; Fedenok, Juliya; Rosa, Aracelli; Peletskaya, Elena; Ryskov, Alexey; Butovskaya, Marina
Abstract Background The oxytocin (OT) system is known to be implicated in the regulation of complex social behavior, particularly empathy and parenting. The goal of this study was to estimate the gender and population differences in polymorphisms of two oxytocin receptor gene SNPs, rs53576 and rs2254298, in four populations. Results These data were compared with each other and with 14 samples from the corresponding regions retrieved from the 1000 Genomes database. Low level of heterozygosity was observed for both SNPs in all populations in this study (rs53576: Catalonian, Hobs = 0.413; Hadza, Hobs = 0.556; sr2254698: Khanty-Mansi, Hobs = 0.250; Datoga, Hobs = 0.550). The amount of variance due to regional variability was almost equal for both SNPs (rs53576: FRT = 0.086, rs2554298: FRT = 0.072), whereas variance for the population level of variability was twice bigger for rs2554298 (rs53576: FST = 0.127, rs2554298: FST = 0.162). Pairwise coefficients of fixation demonstrate that the Hadza were well differentiated from other African populations except of Datoga, the Datoga were weakly differentiated from other African origin populations, the Ob Ugric people were extremely differentiated from all other populations. Catalans were extremely differentiated of Asian populations. Conclusions It is hypothesized on the base of spatial distribution of the evolutionary novel A alleles of the both OXTR gene loci, that the spread of alleles of rs22542298 and rs53376 SNPs may be associated to some extant with manipulation of parental investment in humans.